The Polish Avant-Garde Architecture in the Interwar Period - Regionalism, Nationalism and Modern Architecture - ŚWIT-JANKOWSKA, Barbara (2018)
The article presents the most important Polish architectural achievements from this period and tries to answer the question: which connects regionalism, nationalism and modern architecture. The interwar period was extremely significant moment in the history of architecture. At that time, architectural design was in crisis. Historicism and eclecticism did not work in the post-industrial world. In many countries you can see the search for a new style, on the one hand, adequate for technological development, on the other hand - based on native traditions and referring to regional architecture. The Polish avant-garde architecture in the interwar period was a very interesting phenomenon. As in a nutshell, different trends have focused here - from the still widespread historicism to secession, from modern trends based on the experiences of leading modernists, such as Stanisław and Barbara Brukalscy, Szymon and Helena Syrkusowie, to the Zakopane style, made by Stanislaw Wyspiański. This period in Polish history of architecture not only radically changed the character of Polish city landscape and shaped further developments, it also transformed the experience of reality in a meaningful way. Despite its significant influence on the present shape of our lived environment the importance of the avant-garde remains poorly recognized. Modernist designers usually turned away from historical background, and at the same time they were intensively looking for a justification for the existence of theirs buildings. They tried to do something new and, simultaneously, were afraid of the reaction of society. Regional architecture, with its details and characteristic solutions, has often become the reference point for modern solutions.